Impact of deep-hole opencast blasting on the stability of water dams of a close-by underground coal mine ? Synopsis - C. Sawmliana (The Southern African Institute of Mining and Metallurgy, 2009)
Deep-hole blasting operations in opencast mines are always associated with some annoyance to the surrounding areas in terms of ground vibration, noise, flyrock, etc. These become more severe when underground mines run parallel to them. Blasting in opencast mines may pose danger to the underground mines in terms of roof/side failures, damage of water dams, isolation/ventilation stoppings and other underground installations. The paper discusses a case study in India on the impact of deep-hole blasting in Ramagundam Opencast Project ? III on the stability of various water dams of GDK-6B Incline coal mine operating in close proximity. The stability of underground water dams of GDK-6B Incline mine was endangered due to deep-hole blasting at OCP-III. There were 15 water dams in seam 3 and 16 dams in seam 4 of the underground mine. The physical strength tests using a Schmidt Hammer instrument were carried out in all the 15 water dams of No. 3 seam and 16 water dams of No. 4 seam. The test revealed that there is a decrease in compressive strength values of three dams of seam 3, namely 6A, 6B and 7. Theose three dams were also directly connected to the water source. Water seepage was also observed from the surfaces of the three dams. However, they were found to be stable in accordance with their design parameters and damage point of view while considering a threshold value of ground vibration as 25 mm/s. It was found that the value of tensile stress generated by a vibration of 25 mm/s was much lower (i.e. 0.171N/mm2) than the tensile strength of the two weakest concrete dams (1.85 N/mm2). Ten experimental blasts were conducted at different working benches of the opencast mine and the ground vibration data were recorded in roof and pillars near various underground water dams. The maximum value of vibration data recorded was 5.9 mm/s in roof near dam no. 1 in seam 3 with the dominant peak frequency of 22 Hz. No adverse effect on either of the dams was observed after that blast. During the period of study, no deterioration/adverse impact was found in any dam of the mine. Based on the results of the study and the analyses of the data, optimized blast design parameters and explosives weight per delay were suggested for the opencast mine to maintain the safety of the underground water dams. Keywords: Opencast blasting, damage, water dams, underground mine, ground vibration